Level up to strategic data sharing - Wixom, Barbara Haley, 1969-; Sebastian, Ina M.; Gregory, Robert W.; Piccoli, Gabriele (MIT Sloan Management Review, 2023)
From their research on digital initiatives at 30 organizations, the authors have identified four key practice areas that businesses should focus on to advance their strategic data-sharing capabilities. Using specific examples from Schneider Electric, Elevance Health, and other companies they studied, they describe how strategic data-sharing practices can help businesses better cocreate with customers, engage in novel partnerships, and pursue opportunities in digital ecosystems.